The quest for host targets to combat dengue virus infections - Acosta, Eliana G.; Bartenschlager, Ralf (Current opinion in virology, 2016)
Dengue virus (DENV) is a human threat of increasing importance. Although a tetravalent vaccine has been recently approved, owing to limited efficacy there is still an urgent need for antiviral drugs to prevent or treat DENV infections. Traditionally, antiviral drug discovery has focused on molecules targeting viral factors. However, thus far the identification of direct-acting antiviral drugs with potent DENV pan-serotypic activity has been problematic. An alternative are host-targeting antiviral drugs that hold great promise for broad-spectrum activity. In this review, we summarize cellular factors and pathways required by DENV for efficient replication and in principle suitable for antiviral therapy, including host-directed inhibitors that have even been advanced into clinical trials.
Gesehen am 20.07.2020